Spatially selective modification of PLLA surface: From hydrophobic to hydrophilic or to repellent; Applied Surface Science; Vol. 397 - Bastekova K. Kristina; Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Elashnikov R. Roman; Kunes M. Martin; Kolska Z. Zdenka; Svorcik V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen